Android Applications Security - Paul POCATILU (Informatică economică, 2011)
The use of smartphones worldwide is growing very fast and also the malicious attacks have increased. The mobile security applications development keeps the pace with this trend. The paper presents the vulnerabilities of mobile applications. The Android applications and devices are analyzed through the security perspective. The usage of restricted API is also presented. The paper also focuses on how users can prevent these malicious attacks and propose some prevention measures, including the architecture of a mobile security system for Android devices.